A hydrometallurgical process for the recovery of metal values from spent Cu–Cr catalyst. Issue 2 (3rd April 2018) - Panigrahi, J.; Rout, P.C.; Garnaik, B.; Sarangi, K.
ABSTRACT: The Cu–Cr catalyst has been used in many chemical processes and dumped in the landfill after losing the catalytic property. Owing to the toxicity of chromium, the dumping of catalyst is not environmentally acceptable. So metal values should be removed before disposal. One typical Cu–Cr catalyst was leached with H2 SO4 and from the leach liquor Cu and Cr were extracted using LIX 860N and NaD2EHPA, respectively. The McCabe–Thiele diagram at pH 3.5 with 20% LIX 860N indicated two stages at A:O = 1:1 for quantitative extraction of copper. The stripping of Cu was achieved by 10% H2 SO4 . After the extraction of Cu, the extraction of Cr was carried out with NaD2EHPA. The McCabe–Thiele diagram for Cr extraction with 0.5 M NaD2EHPA at pH 3.0 showed two stages at A:O ratio of 1:1. The loaded organic of chromium was stripped with the mixture of Na2 CO3, NaOH and H2 O2 .